1998 IEEE International Conference on Evolutionary Computation Proceedings. IEEE World Congress on Computational Intelligence (
DOI: 10.1109/icec.1998.699329
|View full text |Cite
|
Sign up to set email alerts
|

Applying genetic algorithms to the U-shaped assembly line balancing problem

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 8 publications
0
31
0
2
Order By: Relevance
“…The chromosomes are defined as precedence feasible sequences of tasks (cf. Leu et al, 1994;Ajenblit and Wainwright, 1998;Sabuncuoglu et al, 2000;Thilakawardana et al, special issue). They are decoded to feasible SALBP-1 solutions, e.g., by applying the task-or station-oriented construction scheme (cf.…”
Section: Encoding Schemes and Genetic Operatorsmentioning
confidence: 92%
“…The chromosomes are defined as precedence feasible sequences of tasks (cf. Leu et al, 1994;Ajenblit and Wainwright, 1998;Sabuncuoglu et al, 2000;Thilakawardana et al, special issue). They are decoded to feasible SALBP-1 solutions, e.g., by applying the task-or station-oriented construction scheme (cf.…”
Section: Encoding Schemes and Genetic Operatorsmentioning
confidence: 92%
“…(7) calculates the fuzzy cycle time of the assembly line. Formula (8) calculates the fuzzy idle percentage of the assembly line. Formula (9) calculates the fuzzy smoothness index.…”
Section: Problem Formulationmentioning
confidence: 99%
“…Therefore, according to the difficulty of such problems, much effort has been made for the development and expansion of heuristic methods such as the Ranked Positional Weighting Technique (RPWT), COMSOAL technique [9], MALB technique [10], MUST technique [11], and LBHA method [12], Critical Path Method (CPM) based approach [13], and also meta-heuristic methods such as genetic algorithm (GA) [8,14], Simulated Annealing (SA) [15], Tabu Search (TS) [16,17], Particle Swarm Optimization (PSO) [18], and Ant Colony Optimization (ACO) [19].…”
Section: Introductionmentioning
confidence: 99%
“…Scholl and Klein [8] proposed the branch and bound procedure ULINO (U Line Optimizer) for the problem. In addition, some other studies on U-type line balancing problem can be found in Miltenburg and Sparling [9], Ohno and Nakade [10], Nakade and Ohno [11], Ohno et al [12], Miltenburg [13], Sparling and Miltenburg [14], Ajenblit and Wainwright [6], Nakade and Ohno [15], Miltenburg [16], Miltenburg [17], Guerriero and Miltenburg [18]. Like the traditional line balancing problem, U-line balancing problem is also NP hard nature (Miltenburg and Sparling [9]).…”
Section: Introductionmentioning
confidence: 99%